Outcomes and Complications With Age in Spondylolisthesis: An Evaluation of the Elderly From the Quality Outcomes Database. Issue 14 (15th July 2020) - Karsy, Michael; Chan, Andrew K.; Mummaneni, Praveen V.; Virk, Michael S.; Bydon, Mohamad; Glassman, Steven D.; Foley, Kevin T.; Potts, Eric A.; Shaffrey, Christopher I.; Shaffrey, Mark E.; Coric, Domagoj; Asher, Anthony L.; et al.
Abstract : Study Design: Prospective database analysis. Objective: To assess the effect of age on patient-reported outcomes (PROs) and complication rates after surgical treatment for spondylolisthesis Summary of Background Data: Degenerative lumbar spondylolisthesis affects 3% to 20% of the population and up to 30% of the elderly. There is not yet consensus on whether age is a contraindication for surgical treatment of elderly patients. Methods: The Quality Outcomes Database lumbar registry was used to evaluate patients from 12 US academic and private centers who underwent surgical treatment for grade 1 lumbar spondylolisthesis between July 2014 and June 2016. Results: A total of 608 patients who fit the inclusion criteria were categorized by age into the following groups: less than 60 (n = 239), 60 to 70 (n = 209), 71 to 80 (n = 128), and more than 80 (n = 32) years. Older patients showed lower mean body mass index ( P < 0.001) and higher rates of diabetes ( P = 0.007), coronary artery disease ( P = 0.0001), and osteoporosis ( P = 0.005). A lower likelihood for home disposition was seen with higher age (89.1% in <60-year-old vs. 75% in >80-year-old patients; P = 0.002). There were no baseline differences in PROs (Oswestry Disability Index, EuroQol health survey [EQ-5D], Numeric Rating Scale for leg pain and back pain) among age categories. A significant improvement for all PROs was seen regardless of age ( P < 0.05), and most patients met minimal clinically important differences (MCIDs) for improvement in postoperative PROs. No differences in hospital readmissions or reoperations were seen among age groups ( P < 0.05). Multivariate analysis demonstrated that, after controlling other variables, a higher age did not decrease the odds of achieving MCID at 12 months for the PROs. Conclusion: Our results indicate that well-selected elderly patients undergoing surgical treatment of grade 1 spondylolisthesis can achieve meaningful outcomes. This modern, multicenter US study reflects the current use and limitations of spondylolisthesis treatment in the elderly, which may be informative to patients and providers. Level of Evidence: 4 Abstract : Supplemental Digital Content is available in the textA multicenter analysis of the effect of age on patient-reported outcomes (PROs) and complications in patients with degenerative grade 1 spondylolisthesis using the Quality Outcomes Database showed all PROs significantly improved postoperatively. Most patients met minimal clinically important differences independent of age and other clinical variables. This study supports surgical treatment for well-selected elderly patients with spondylolisthesis and suggests that age should not be a contraindication to treatment.